2013
DOI: 10.3390/jcm2040264
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Epithelial-to-Mesenchymal Transition (EMT) and Mesenchymal-to-Epithelial Transition (MET) in Breast Cancer Bone Metastasis: Potential Targets for Prevention and Treatment

Abstract: Many studies have revealed molecular connections between breast and bone. Genes, important in the control of bone remodeling, such as receptor activator of nuclear kappa (RANK), receptor activator of nuclear kappa ligand (RANKL), vitamin D, bone sialoprotein (BSP), osteopontin (OPN), and calcitonin, are expressed in breast cancer and lactating breast. Epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) effectors play critical roles during embryonic development, postnatal growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 136 publications
(157 reference statements)
1
57
0
Order By: Relevance
“…Changes observed in EMT markers such as increased E-cadherin and decreased Vimentin expression further suggest changes noted are secondary to differentiation. As previously described functional loss or downregulation of E-cadherin from epithelial cells is a hallmark of EMT [22]. GFAP is a protein largely found in astrocytes and a protein marker of differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…Changes observed in EMT markers such as increased E-cadherin and decreased Vimentin expression further suggest changes noted are secondary to differentiation. As previously described functional loss or downregulation of E-cadherin from epithelial cells is a hallmark of EMT [22]. GFAP is a protein largely found in astrocytes and a protein marker of differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…Metastasis-related pathways, such as the transition between the epithelial and mesenchymal phenotype, were altered by inflammatory molecules (29). Tumor cells secrete interleukin (IL)-6 and IL-8, which are important mediators of EMT in breast cancer (30). In addition, tumor cells secrete IL-6 and IL-8, which affect the phenotypes in an autocrine manner and IL-8 promotes the mesenchymal phenotype (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that OPN and αvβ3 integrin interaction may mediate many of the activities necessary for this initial step in the bone metastasis of malignancies. A number of studies showed that overexpression of OPN were determinative of a high incidence of bone metastases in breast cancer (25). Likewise, in prostate cancer, activation of αvβ3 integrin allows cancer cells to adhere and migrate to bone matrix at early stages of skeletal metastasis (26).…”
Section: Figure 4 Effect Of Opn and ανβ3 Integrin On Adhesion Of A54mentioning
confidence: 99%